Pemahaman Doktrin Manusia dan Dosa dalam Perspektif Teologi Kristen - Krista Nessa; Nailda, Nailda; Peni Aprilia (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The understanding of the doctrine of humanity and sin in Christian theology reveals the essence of human nature and the need for divine redemption. This study aims to examine theological perspectives on human nature and sin, focusing on the relationship between the Imago Dei and the fall of humanity. Using a qualitative descriptive approach through literature review, the research analyzes biblical texts and theological interpretations from various Christian scholars. The results show that humans, created in the image and likeness of God, were originally good and endowed with moral and spiritual capacity. However, through sin, humans experienced separation from God and moral corruption. Nevertheless, God’s grace through Jesus Christ enables the restoration of humanity’s divine image and reconciles the broken relationship with the Creator. The study highlights that understanding these doctrines helps believers realize their dependence on God’s grace, leading to repentance, transformation, and ethical living. The implication encourages Christians to maintain a responsible, spiritual, and moral life as a reflection of the renewed image of God within them.